1998
DOI: 10.1103/physrevb.57.10893
|View full text |Cite
|
Sign up to set email alerts
|

Row-switched states in two-dimensional underdamped Josephson-junction arrays

Abstract: When magnetic flux moves across layered or granular superconductor structures, the passage of vortices can take place along channels which develop finite voltage, while the rest of the material remains in the zerovoltage state. We study analytically an example of such mixed dynamics: the row-switched ͑RS͒ states in underdamped two-dimensional Josephson arrays, driven by a uniform dc current under external magnetic field but neglecting self-fields. The governing equations are cast into a compact differential-al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 54 publications
(161 reference statements)
0
21
0
Order By: Relevance
“…For underdamped junctions, these states manifest themselves by various branches on the current-voltage (I-V ) characteristics. The hysteretic switching between branches has been found in stacks of Josephson tunnel junctions [4], layered high-temperature superconductors [5] and twodimensional (2D) Josephson junction arrays [2,3,7,8].In 2D arrays, this switching effect appears in the form of row switching when a voltage drop in array occurs on individual rows of junctions perpendicular to the direction of the bias current. A typical behavior found in both experiments [7] and in numerical simulations [3,9] is that the number of rows switched to resistive state and, even more important, their distribution inside the array can change during sweeping the I-V curve.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For underdamped junctions, these states manifest themselves by various branches on the current-voltage (I-V ) characteristics. The hysteretic switching between branches has been found in stacks of Josephson tunnel junctions [4], layered high-temperature superconductors [5] and twodimensional (2D) Josephson junction arrays [2,3,7,8].In 2D arrays, this switching effect appears in the form of row switching when a voltage drop in array occurs on individual rows of junctions perpendicular to the direction of the bias current. A typical behavior found in both experiments [7] and in numerical simulations [3,9] is that the number of rows switched to resistive state and, even more important, their distribution inside the array can change during sweeping the I-V curve.…”
mentioning
confidence: 99%
“…For underdamped junctions, these states manifest themselves by various branches on the current-voltage (I-V ) characteristics. The hysteretic switching between branches has been found in stacks of Josephson tunnel junctions [4], layered high-temperature superconductors [5] and twodimensional (2D) Josephson junction arrays [2,3,7,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The abundant nonlinear properties embodied in this model is studied intensively [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…For instance in a recent experiment [13] it has shown that individual rows seem capable to phase-lock, so that the whole system is better described in terms of oscillators constituted by rows than by considering the individual junctions as elementary oscillators. Also in theoretical investigations, such as those of Barahona and Watanabe [14], the motion of°uxons across the arrays, in absence of microwave excitations, has been handled starting from the dynamics of the elementary rows.…”
Section: Introductionmentioning
confidence: 99%